Religion in the Postmodern Thought - Zarkasyi, Hamid Fahmy (Center of Islamic and Occidental Studies, 2024)
As understood, postmodernism is a worldview that borrows its nomenclature from the era after modernism. It became a progressive thought with ideas notable for denouncing absolute truth. This article aims to explain what postmodernism is and how religion is understood by its people, mainly by referring to the thoughts of postmodern philosophers who played an important role in undermining religious traditions through the devaluation of religious values, namely Nietzsche (1884-1900), Wittgenstein (1889-1951) and Heidegger (1889-1976). In the discussion, it is found that postmodernism has a distinctive conception of God and religion. It dissolves the highest values, which is God, to which all other value may refer to as their foundations. Since human reason cannot conceive the nature of God, postmodern intellect disestablishes the metaphysical way of thinking. Thus, the postmodernists get it religion in so diverse way that conflicting to the predominant conviction of theologians.